Evaluation of the impact of preoperative use of dexamethasone and cyclobenzaprine in surgical extraction of lower third molars on trismus by electromyographic analysis - Raldi, Fernando Vagner [UNESP]; Nascimento, Rodrigo Dias [UNESP]; Sato, Fábio Ricardo Loureiro [UNESP]; Santos, Lucio Murillo [UNESP]; Amorim, José Benedito Oliveira [UNESP]; de Moraes, Michelle Bianchi [UNESP] (Springer Nature, 2019)
Purpose: The aim of this study was to evaluate the influence of cyclobenzaprine and dexamethasone on ​the electrical activity of the masticatory muscles in patients who had undergone lower third molar surgery. Methods: Thirty bilateral impacted lower third molars with indication of extraction were randomised into three groups: the control group, the dexamethasone, and the cyclobenzaprine group. To obtain muscular electrical activity and mouth opening, an electromyographic device was used at mandibular rest and maximum voluntary contraction and compared pre- and post-operatively. Results: During muscle contraction, no significant difference was observed in the electromyographic records on the non-operated side. On the operated side, there was a reduction in electrical activity for both drugs pre-operatively and immediately post-operatively compared to the control group. All pharmacological agents promoted a higher mouth opening compared to control group. Conclusion: The results suggest that dexamethasone and cyclobenzaprine may be useful as an adjuvant in the prevention of motor dysfunctions in third molar surgery.
Keywords: Corticosteroid; Electromyography; Muscle relaxants; Third molars